Analysis of Costs in an Algebra I Curriculum Effectiveness Study - Daugherty, Lindsay (RAND Corporation, 2012)
Carnegie Learning's Cognitive Tutor Algebra I (CTAI) curriculum is a technology-based curriculum that combines classroom instruction with individualized instruction by a computer-based tutor. This report examines the cost of implementing CTAI and comparison algebra I curricula, including costs associated with textbooks and software, computers, and teacher training.